2019
DOI: 10.1080/15384047.2019.1617569
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LINC00511 promotes radiosensitivity of thyroid carcinoma cells via suppressing JAK2/STAT3 signaling pathway

Abstract: Thyroid carcinoma is the most widespread malignancy in endocrine system with the increasing incidence. Despite of the advanced approaches to the management of thyroid carcinoma, the therapeutic effects remain unpleasant largely due to the radiosensitivity of thyroid carcinoma cells. LncRNAs play important part in the tumorigenesis and development, especially in the radiosensitivity of tumor cells. However, their roles in thyroid carcinoma still needed to be explored deeply. The purpose of our research is to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…LINC00511 shows cancer promoting activity because it was shown that LINC00511 is up-expressed in many cancers and related to several features of cancer, such as proliferation (Sun et al, 2016 ; Li et al, 2018 ; Lu et al, 2018 ; Deng et al, 2019 ; Liu et al, 2019 ; Mao et al, 2019 ; Yu et al, 2019 ; Zhang J. et al, 2019 ; Zhu et al, 2019 ), apoptosis (Sun et al, 2016 ; Li et al, 2018 ; Deng et al, 2019 ; Mao et al, 2019 ; Wang R. P. et al, 2019 ; Zhang J. et al, 2019 ; Zhu et al, 2019 ), invasion (Sun et al, 2016 ; Lu et al, 2018 ; Mao et al, 2019 ; Quan et al, 2019 ; Wang R. P. et al, 2019 ; Yu et al, 2019 ; Zhu et al, 2019 ), radio-resistance (Chen et al, 2019 ; Liu et al, 2019 ), migration (Sun et al, 2016 ; Mao et al, 2019 ; Wang R. P. et al, 2019 ; Yu et al, 2019 ; Zhu et al, 2019 ), drug resistance (Mao et al, 2019 ), metastasis (Deng et al, 2019 ; Zhu et al, 2019 ), and growth (Sun et al, 2016 ; Deng et al, 2019 ; Wang R. P. et al, 2019 ). High LINC00511 expression is significantly correlated with TNM classification, lymph node metastasis, and short OS among patients with clear cell renal cell carcinoma (Deng et al, 2019 ) and NSCLC (Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00511 shows cancer promoting activity because it was shown that LINC00511 is up-expressed in many cancers and related to several features of cancer, such as proliferation (Sun et al, 2016 ; Li et al, 2018 ; Lu et al, 2018 ; Deng et al, 2019 ; Liu et al, 2019 ; Mao et al, 2019 ; Yu et al, 2019 ; Zhang J. et al, 2019 ; Zhu et al, 2019 ), apoptosis (Sun et al, 2016 ; Li et al, 2018 ; Deng et al, 2019 ; Mao et al, 2019 ; Wang R. P. et al, 2019 ; Zhang J. et al, 2019 ; Zhu et al, 2019 ), invasion (Sun et al, 2016 ; Lu et al, 2018 ; Mao et al, 2019 ; Quan et al, 2019 ; Wang R. P. et al, 2019 ; Yu et al, 2019 ; Zhu et al, 2019 ), radio-resistance (Chen et al, 2019 ; Liu et al, 2019 ), migration (Sun et al, 2016 ; Mao et al, 2019 ; Wang R. P. et al, 2019 ; Yu et al, 2019 ; Zhu et al, 2019 ), drug resistance (Mao et al, 2019 ), metastasis (Deng et al, 2019 ; Zhu et al, 2019 ), and growth (Sun et al, 2016 ; Deng et al, 2019 ; Wang R. P. et al, 2019 ). High LINC00511 expression is significantly correlated with TNM classification, lymph node metastasis, and short OS among patients with clear cell renal cell carcinoma (Deng et al, 2019 ) and NSCLC (Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanistic studies revealed that LINC00511 could act at transcriptional and post-transcriptional level. Moreover, LINC00511 was found to interact with a variety of signaling pathways including JAK2/STAT3 [ 45 ], Wnt/β-catenin [ 46 ], and PTEN/AKT/FOXO1 [ 47 ], in the pathogenesis of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 – 16 ] Jiang et al [ 36 ] also suggested that silencing LINC00511 would suppress the proliferation, migration, and epithelial-mesenchymal transition of lung cancer cells by modulating the PTEN/AKT/FOXO1 axis. Moreover, Li et al [ 37 ] found that overexpression of LINC00511 enhanced the proliferation and invasion of glioma cells through inhibition of miR-124-3p and concomitant upregulation of cyclin D2. [ 37 ] In OC, LINC00511 was found to interact with enhancer of zeste homologue 2 to repress P21 expression, thereby augmenting the viability and invasive ability of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al [ 37 ] found that overexpression of LINC00511 enhanced the proliferation and invasion of glioma cells through inhibition of miR-124-3p and concomitant upregulation of cyclin D2. [ 37 ] In OC, LINC00511 was found to interact with enhancer of zeste homologue 2 to repress P21 expression, thereby augmenting the viability and invasive ability of cancer cells. [ 16 ] Yu et al [ 10 ] and Mao et al [ 9 ] also demonstrated that LINC00511 could promote the proliferation, migration, invasion, and resistance to paclitaxel in CC cells by upregulating matrix metalloproteinase-9, P-glycoprotein, Bcl-2, and a multidrug resistance protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation